Magnet mobility myths: exploring geographical mobility amongst people experiencing, or at-risk of, homelessness in Australia - Batterham, Deb (My University, 2022)
It is often assumed that people experiencing homelessness gravitate to large cities and central city areas because of the concentration of homelessness services — a so-called magnet or honeypot effect. Yet little is actually known about how people experiencing homelessness move across space over time. This article explores this geography by comparing the mobility of those experiencing homelessness, those ‘at-risk’, and those renting privately in Australia, between waves in two Australian panel surveys: Journeys Home and the Household, Income and Labour Dynamics in Australia (HILDA). Results suggest that while people experiencing homelessness are more likely to move than the other two groups, they more similarly short distances and appear more likely to move for reasons such as relationship breakdown, eviction and to escape violence. While some evidence of movement to areas with particular characteristics (sorting) was detected amongst those at-risk and those renting privately, this was not the case for those experiencing homelessness. Results do not support the contention that people experiencing homelessness gravitate to central urban areas well-resourced with homelessness services over time. The findings challenge assumptions about magnet effects and homelessness and have important implications for the provision and delivery of homelessness services in Australia and beyond.
International Journal of Housing Policy
Keywords: Housing, communities and neighbourhoods; Migration and settlement